The cost of antenatal care in Beijing: a cross-sectional study - Zhang, ZiQi; Shao, Yu; Ma, WenLin; Gao, Qun; Song, Bo; Qu, ShuiLing; Wang, AiLing (BMC public health, 2025)
Medical and non-medical expenses could be incurred during antenatal care, however, few studies about it in Beijing were found. Hence, this study assesses the cost of antenatal care in Beijing and explores it's influencing factors, aiming to inform targeted strategies. A cross-sectional study was conducted in Beijing from October 14 to December 16, 2024. A cluster sampling technique was used to select subjects. Data were collected through an in-person questionnaire. The cost of antenatal care includes direct costs and indirect costs. The demographic characteristics were statistically described. Univariate analysis and quantile regression model were applied. A total of 253 pregnant women in Beijing were recruited in this study, and the cost of antenatal care was USD 2,198. The results of the univariate analysis showed statistically significant differences between antenatal cost and pregnant women's age, family size, gravidity, parity, pregnancy complication, whether or not to hire caregivers, whether the caregiver missed work or not and outpatient visits times (P < 0.05). The results of the quantile regression modeling showed that age, pregnancy complications, whether or not to hire caregivers, whether the caregiver missed work or not, and outpatient visits times can affect the cost of antenatal care at one or more quantiles (P < 0.05). There are high proportion of direct medical costs. It is suggested that reducing the lost wages of pregnant women and caregivers by increasing leaves for them, and controlling complications to alleviate the financial burden of pregnancy.